Gender differences in occupational stress among correctional officers - Gross, George R. (American journal of criminal justice, 1994)
Stress that relates to the work environment has received increasing attention. However, research on gender differences and work-related stress is limited. Previous research has shown that female correctional officers tend to experience higher levels of stress than do their male counterparts. However, this research found that female and male correctional officers experience similar levels of stress as measured both objectively and subjectively. Ulis result should not be surprising given the existing working conditions in most prisons today.